Honeybee microbiome is stabilized in the presence of propolis. (6th May 2020) - Saelao, Perot; Borba, Renata S.; Ricigliano, Vincent; Spivak, Marla; Simone-Finstrom, Michael
Abstract : Honeybees have developed many unique mechanisms to help ensure the proper maintenance of homeostasis within the hive. One method includes the collection of chemically complex plant resins combined with wax to form propolis, which is deposited throughout the hive. Propolis is believed to play a significant role in reducing disease load in the colony due to its antimicrobial and antiseptic properties. However, little is known about how propolis may interact with bee-associated microbial symbionts, and if propolis alters microbial community structure. In this study, we found that propolis appears to maintain a stable microbial community composition and reduce the overall taxonomic diversity of the honeybee microbiome. Several key members of the gut microbiota were significantly altered in the absence of propolis, suggesting that it may play an important role in maintaining favourable abundance and composition of gut symbionts. Overall, these findings suggest that propolis may help to maintain honeybee colony microbial health by limiting changes to the overall microbial community.